Penggunaan Mainan “Spider Fidget Mathic” pada Siswa Kelas 3 MI Tarbiyatul Huda - Alvianita, Mahda; Aisyah, Azizah Nur; Ananda, Romadhona Regita (LPPM Universitas Muhadi Setiabudi, 2024)
Learning media props convey information about learning and deliver learning material. Learning media should be conceptualized as customized toys that are innovated into learning toys that are close to children's characteristics, methods and learning styles. Because the stimulus chosen for elementary school children should be contextual, interesting, and preferably contemporary so as to stimulate students' curiosity so that they can achieve better learning outcomes. Community service activity on October 25 2022 at MI Tarbiyatul Huda Jombang Regency as an activity to implement the use of learning media in the form of the